Challenges in emergency peripartum hysterectomy in initial phase of obstetrics practice: series of 9 cases - Deka, Ranima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Emergency peripartum hysterectomy (EPH) is usually done to control bleeding of life threatening peripartum haemorrhage when all of all conservative measures fail. It is a technically demanding surgical procedure that carries high rate morbidity and mortality. From January 2016 to January 2019 data of all EPH done by our in different hospital of the city is collected. Total of 9 patients fulfil the definition of EPH. We tried with all sorts as bimanual uterine compression, administration of oxytocin or prostaglandins, uterine packing, compression sutures such as the B-Lynch brace suture before operation to controlled haemorrhage. On failure of the above mentioned measure we plan EPH. We took help of a surgeon in all of 9 cases. Bleeding is the greatest challenge in our series. Out of 9 patient 8 patient survived, one patient died of bleeding due to DIC. There is one urinary bladder injury and repaired intraoperatively. All patient has minor wound infection and that was managed with oral antibiotics and wound dressings. Postoperative average ICU stay was 3 days. Average PRBC transfusion is 4 units and two patient required FFP transfusion. In one patient we did subtotal hysterectomy and in rest all other patient we did total hysterectomy. With good team work EPH can be done with acceptable morbidity and mortality.